Doit-on considérer les collections de tableaux comme des « meubles meublants » ? - Comtois, Roger (Assurances, 1983)
We asked Me Roger Comtois the following question: should collections of paintings be considered as “furniture”, as normally understood? The writer is kind enough to give his reply in this text. He distinguishes between what is intended to decorate the house or apartment, and what really constitutes a collection of works of art put together by the owner over the years and which may he on his premises or elsewhere.